PERANAN KONSERVATISME AKUNTANSI TERHADAP GENDER DIVERSITY DAN KINERJA KEUANGAN - Anggraini, Fivi; Yanto, Febri (Jurnal Kajian Akuntansi dan Auditing, 2024)
The current trend is for women to hold board positions due to legislation to increase the role of women on company boards. The diversity of women's boards can improve a company's ability to achieve financial performance. This study aims to determine the effect of gender diversity on financial performance through accounting conservatism as a mediating variable in manufacturing companies in the consumer goods sector in Indonesia. The sample of this research is 33 manufacturing companies in the consumer goods sub-sector that are listed on the Indonesia Stock Exchange (IDX) during 2016-2020. The results of this study prove that the role of accounting conservatism is able to mediate the relationship between gender diversity and financial performance. This proves that greater gender diversity increases profits and supports shareholder value economics because it emphasizes the need for gender balance between men and women to optimize the company's financial performance. The implication is that various company boards will more optimally determine accounting policies and apply conservative principles in managing the company. This study recommends that the company evaluates and communicates the level of gender diversity within the company.